2022
DOI: 10.3390/pr10112428
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Diverse Array of Nitrite Scavengers in Solution and Solid State: A Study of Inhibitory Effect on the Formation of Alkyl-Aryl and Dialkyl N-Nitrosamine Derivatives

Abstract: The ubiquitous presence of mutagenic and potentially carcinogenic N-nitrosamine impurities in medicines has become a major issue in the pharmaceutical industry in recent years. Rigorous mitigation strategies to limit their amount in drug products are, therefore, needed. The removal of nitrite, which is a prerequisite reagent for the N-nitrosation of amines, has been acknowledged as one of the most promising strategies. We have conducted an extensive literature search to identify nineteen structurally diverse n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Current understanding is that nitrite is the limiting reagent in the formation of NDSRIs and thus its concentration determines the maximum amount of N -nitrosamine that can form in the drug product . It is important to note however that only a fraction of the total nitrite effectively leads to N -nitrosamine impurities under usual formulation and storage conditions, with the levels depending on the reactivity of the vulnerable secondary amine: typically a few percent for aliphatic amines, whereas the extent of nitrosation of aromatic derivatives can be much higher (e.g., 25% nitrosation of N -methyl phenylamine) …”
Section: Mitigation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Current understanding is that nitrite is the limiting reagent in the formation of NDSRIs and thus its concentration determines the maximum amount of N -nitrosamine that can form in the drug product . It is important to note however that only a fraction of the total nitrite effectively leads to N -nitrosamine impurities under usual formulation and storage conditions, with the levels depending on the reactivity of the vulnerable secondary amine: typically a few percent for aliphatic amines, whereas the extent of nitrosation of aromatic derivatives can be much higher (e.g., 25% nitrosation of N -methyl phenylamine) …”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…It is plausible that this is due to the restricted mobility of the two reacting species (i.e., nitrite and vulnerable amine) in the solid phase and the heterogeneous nature of the system where reactants may be immobilized in highly crystalline phases or in the core of large particles. Other factors that may play a role here are the limited stability of nitrite and/or some N -nitrosamines. , Data in this area are scarce, and more research is necessary to clarify these aspects.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…So, if we cannot control via reduction/elimination of nitrite in excipients, what other options exist? Tantalizingly, research showed that nitrosamine formation could be inhibited by the use a scavenger, , but to date there is not one example of an approved product where such an approach has been utilized. Thus, the idea that tens of thousands of products could be reformulated to include a scavenger is impossible, especially when other considerations relating to studies needed to support such a process change are taken into consideration.…”
Section: N-nitrosamines Current Challengesmentioning
confidence: 99%
“…Subsequent investigations revealed that APIs, which possess vulnerable secondary or tertiary amine moieties, can also be susceptible to N -nitrosation, forming nitroso-API impurities ( N -nitrosamine drug substance-related impurities, NDSRIs) . In the case of formation in the drug product itself, there is limited opportunity to mitigate the risk of NDSRI formation due to the lack of opportunity for purging . Such cases have already triggered recalls of drugs from the market…”
Section: Introductionmentioning
confidence: 99%